2023
DOI: 10.18196/jai.v24i2.16562
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of strategic management accounting implementation in Higher Education Institutions (HEIs) in Indonesia

Abstract: Research aims: This study aims to examine determinants of strategic management accounting implementation, including market orientation, top management characteristics, strategy, and information technology.Design/Methodology/Approach: This research was conducted in higher education institutions (HEIs) in some areas, covering Sumatra, Java, Bali, Nusa Tenggara, Kalimantan, Sulawesi, and Papua. The research respondents were 368 HEIs leaders. Data were obtained by distributing questionnaires, and the hypotheses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This research adopts a cross-sectional study design to collect data from various stakeholders within multiple HEIs. The cross-sectional approach allows for the collection of data at a single point in time, providing a snapshot of the current state of ISG effectiveness across different institutions [13], [14], [15].…”
Section: A Research Designmentioning
confidence: 99%
“…This research adopts a cross-sectional study design to collect data from various stakeholders within multiple HEIs. The cross-sectional approach allows for the collection of data at a single point in time, providing a snapshot of the current state of ISG effectiveness across different institutions [13], [14], [15].…”
Section: A Research Designmentioning
confidence: 99%
“…A study (Bluwstein et al, 2021) using macro-financial data from 17 countries from 1870 to 2016 approached the machine learning model in the stock market crisis study, where it applied one of the ensemble models, Extremely Randomized Trees (Extra Trees) and produced the most accurate results. Tölö (2020), in predicting systemic financial crises one to five years ahead, which includes the crisis dates and annual macroeconomic series of 17 countries over the period 1870-2016, found that machine learning models can be significantly improved by using Long-Short Term Memory (RNN-LSTM) and Gated Recurrent Unit (RNN-GRU) neural nets (Marlina et al, 2023). In another study, Coffinet and Kien (2019) focused on detecting rare events in banking crisis cases, using data collected from 32 European and non-European countries from 2010 to 2017 (Pratama & Wijaya, 2023).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%